2010
DOI: 10.1007/s00335-010-9273-7
|View full text |Cite
|
Sign up to set email alerts
|

SYSGENET: a meeting report from a new European network for systems genetics

Abstract: The first scientific meeting of the newly established European SYSGENET network took place at the Helmholtz Centre for Infection Research (HZI) in Braunschweig, April 7-9, 2010. About 50 researchers working in the field of systems genetics using mouse genetic reference populations (GRP) participated in the meeting and exchanged their results, phenotyping approaches, and data analysis tools for studying systems genetics. In addition, the future of GRP resources and phenotyping in Europe was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Host defense is strongly influenced by genetic differences and several studies have shown that the genetic background and sequence difference among humans and other host species modulate susceptibility and resistance to infectious diseases, allergens, and xenobiotics. Systems genetics is a modern extension of complex trait analysis that jointly analyzes and integrates large sets of genotypes and phenotypes to explain and predict variation in outcome measures and disease severity (for review see [ 1 , 2 ]). A typical systems genetics study relies on extensive single nucleotide polymorphism (SNP) data sets, matched data on RNA expression in key cells, tissues, or organs and a core set of key dependent measures such as disease susceptibility [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Host defense is strongly influenced by genetic differences and several studies have shown that the genetic background and sequence difference among humans and other host species modulate susceptibility and resistance to infectious diseases, allergens, and xenobiotics. Systems genetics is a modern extension of complex trait analysis that jointly analyzes and integrates large sets of genotypes and phenotypes to explain and predict variation in outcome measures and disease severity (for review see [ 1 , 2 ]). A typical systems genetics study relies on extensive single nucleotide polymorphism (SNP) data sets, matched data on RNA expression in key cells, tissues, or organs and a core set of key dependent measures such as disease susceptibility [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…family (Peirce et al, 2004), the Hybrid Mouse Diversity Panel (Bennett et al, 2015;Ghazalpour et al, 2012), and the Collaborative Cross (Churchill et al, 2004;Schughart and Williams, 2017;Valdar et al, 2006). The main limitation has been relatively modest mapping power and precision-a simple problem caused by small numbers of strains.…”
Section: Numbers Of Strains and Replicates In Bxdmentioning
confidence: 99%
“…Pearson’ correlation graphs were built constructed using the database obtained from the hypothalamus (INIA Hypothalamus Affy MoGene 1.0 ST (Nov10) database), striatum, liver, retina, spleen, neocortex, and pituitary of BXD inbred family, as previously published (Andreux et al, ). Datasets from a BXD published phenotypes (Schughart & Consortium, ) were also analyzed. The human dataset from hypothalamic tissue (GTEx Human Hypothalamus (Mar14) RPKM Log2 database) and 26 other tissues were evaluated, as previously published (GTEx Consortium, ) by Pearson’s correlations.…”
Section: Methodsmentioning
confidence: 99%
“…Datasets from a BXD published phenotypes (Schughart & Consortium, 2010) were also analyzed. The human dataset from hypothalamic tissue (GTEx Human Hypothalamus (Mar14) RPKM Log2 database) and 26 other tissues were evaluated, as previously published (GTEx Consortium, 2013) by Pearson's correlations.…”
Section: Bioinformatics Analysismentioning
confidence: 99%